Governing military technologies in the 21st Century: ethics and operations - O'Meara, Richard Michael; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Governing Military Technologies in the 21st Century is one of the first books to tackle the big five technological threats all in one place: nanotech, robotics, cyberwar, human enhancement, and, non-lethal weapons, weaving a historical, legal, and sociopolitical fabric into a discussion of their development, deployment, and, potential regulation.
Keywords: Science; Science, general